2015
DOI: 10.1136/bmjquality.u209711.w4036
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care discharges: improving the quality of clinical handover through changes to discharge documentation

Abstract: Patients who have stepped down from intensive care tread a precarious clinical course, and the handover of care between clinical teams at this point should be treated as a high risk event. Poor handover can leave patients vulnerable to suboptimal care and preventable harm. Properly structured written discharge summaries have been shown to improve information transfer and quality of care. The National Institute for Health and Care Excellence (NICE) has published guidelines entitled “Acute illness in adults in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…On the other hand, the items with negative weights, adding up regular and poor, are related to Interaction and multidisciplinary activity (59.9%) and Care monitoring and transfer (28.5%). These questions seem to advance timidly in view of the complexity of the interventions and the need for knowledge articulation and team integration 23 .Therefore, teaching and interdisciplinary practice have been investigated, and are currently encouraged to improve the fragmented health systems, constituting a feasible and efficient service provision model 24 .Another challenge evidenced in this study that is in accordance with other findings 25 is related to the transfer of information among clinical teams through formal registers, reducing adverse incidents and improving the continuity of health care.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, the items with negative weights, adding up regular and poor, are related to Interaction and multidisciplinary activity (59.9%) and Care monitoring and transfer (28.5%). These questions seem to advance timidly in view of the complexity of the interventions and the need for knowledge articulation and team integration 23 .Therefore, teaching and interdisciplinary practice have been investigated, and are currently encouraged to improve the fragmented health systems, constituting a feasible and efficient service provision model 24 .Another challenge evidenced in this study that is in accordance with other findings 25 is related to the transfer of information among clinical teams through formal registers, reducing adverse incidents and improving the continuity of health care.…”
Section: Discussionsupporting
confidence: 79%
“…Few studies have examined the role of structured discharge summaries for patients with high-risk medical conditions such as diabetes [17,31]. In addition, studies on the communication and documentation of essential information during discharge are consistently lacking in the literature [17,[32][33][34]. Kripalani et al reported in 2007 that direct communication between care settings occurred infrequently and discharge summaries often lacked details on diagnostic test results, treatment or hospital course, discharge medications, pending test results, patient counselling, and follow-up plans [35].…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Several groups have studied the impact of a patient discharge summary generated at transfers in care, and have found that providing diagnosis-specific discharge summaries positively affects patient satisfaction and patient safety, improves communication among care providers, empowers patients to better self-manage their symptoms, and results in fewer hospital re-admissions. 2,7,8 For patients receiving radiation treatment, the end of a course of radiotherapy often marks a transition from active treatment, where patients are seen daily by radiation therapists, nurses and oncologists, to a period of follow-up where patient are not coming into the cancer centre on a daily basis. In particular, the 2 weeks following radiotherapy can be associated with increased side effects.…”
Section: Introductionmentioning
confidence: 99%